The arithmetic sequence 2, 12, 36, 80.... Is a function of?
A. ${n^2}(n - 1)$
B. $n(n + 1)$
C. ${n^2}(n + 1)$
D. ${n^2}(n + 2)$
Answer
Verified
478.8k+ views
Hint: This question can be done by putting the value of terms of the sequence in given options and then we can find out the correct option. Basically we have to find the $n^{th}$ term of the sequence.
Complete step-by-step answer:
The arithmetic sequence is given by 2, 12, 36, and 80 here ${T_1} = 2, {T_2} = 12, {T_3} = 36, {T_4} = 80$
Now we will put n=1 in ${n^2}(n - 1)$ and see if the result is coming 2 or not.
$ \Rightarrow {(1)^2}(1 - 1) = 0$
Therefore this function is incorrect as the first term which should be 2 is not coming here.
Now we will put n=1 in $n(n + 1)$ and see if the result is coming 2 or not.
$ \Rightarrow 1(1 + 1) = 2$
Therefore this function can be correct as the first term which should be 2 is coming here but we have to check the other functions as well.
Now we will put n=1 in ${n^2}(n + 1)$ and see if the result is coming 2 or not.
$ \Rightarrow {(1)^2}(1 + 1) = 2$
Therefore this function can be correct as the first term which should be 2 is coming here but we have to check the other functions as well.
Now we will put n=1 in ${n^2}(n + 2)$ and see if the result is coming 2 or not.
$ \Rightarrow {(1)^2}(1 + 2) = 3$
Therefore this function is incorrect as the first term which should be 2 is not coming here.
After this two options are eliminated that are options (A) and (D). Now we will do same process with other two options that are (B) and (C) but now we will put n=2
Now we will put n=2 in $n(n + 1)$ and see if the result is coming 12 or not.
$ \Rightarrow 2(2 + 1) = 6$
Therefore this function is incorrect as the second term which should be 12 is not coming here.
Now we will put n=2 in ${n^2}(n + 1)$ and see if the result is coming 12 or not.
$ \Rightarrow {(2)^2}(2 + 1) = 4 \times 3 = 12$
Therefore this function is correct as required second term 12 is coming here.
So, the correct answer is “Option C”.
Note: Students may likely to make mistake by trying to solve this question by applying direct formula of $n^{th}$ term of an A.P (arithmetic progression) which is given by ${T_n} = a + (n - 1)d$ where a= first term of the sequence and d=common difference which is given by $d = {T_n} - {T_{n - 1}}$. But here the full sequence is not given so the number of terms is not given so this formula cannot be applied directly.
Complete step-by-step answer:
The arithmetic sequence is given by 2, 12, 36, and 80 here ${T_1} = 2, {T_2} = 12, {T_3} = 36, {T_4} = 80$
Now we will put n=1 in ${n^2}(n - 1)$ and see if the result is coming 2 or not.
$ \Rightarrow {(1)^2}(1 - 1) = 0$
Therefore this function is incorrect as the first term which should be 2 is not coming here.
Now we will put n=1 in $n(n + 1)$ and see if the result is coming 2 or not.
$ \Rightarrow 1(1 + 1) = 2$
Therefore this function can be correct as the first term which should be 2 is coming here but we have to check the other functions as well.
Now we will put n=1 in ${n^2}(n + 1)$ and see if the result is coming 2 or not.
$ \Rightarrow {(1)^2}(1 + 1) = 2$
Therefore this function can be correct as the first term which should be 2 is coming here but we have to check the other functions as well.
Now we will put n=1 in ${n^2}(n + 2)$ and see if the result is coming 2 or not.
$ \Rightarrow {(1)^2}(1 + 2) = 3$
Therefore this function is incorrect as the first term which should be 2 is not coming here.
After this two options are eliminated that are options (A) and (D). Now we will do same process with other two options that are (B) and (C) but now we will put n=2
Now we will put n=2 in $n(n + 1)$ and see if the result is coming 12 or not.
$ \Rightarrow 2(2 + 1) = 6$
Therefore this function is incorrect as the second term which should be 12 is not coming here.
Now we will put n=2 in ${n^2}(n + 1)$ and see if the result is coming 12 or not.
$ \Rightarrow {(2)^2}(2 + 1) = 4 \times 3 = 12$
Therefore this function is correct as required second term 12 is coming here.
So, the correct answer is “Option C”.
Note: Students may likely to make mistake by trying to solve this question by applying direct formula of $n^{th}$ term of an A.P (arithmetic progression) which is given by ${T_n} = a + (n - 1)d$ where a= first term of the sequence and d=common difference which is given by $d = {T_n} - {T_{n - 1}}$. But here the full sequence is not given so the number of terms is not given so this formula cannot be applied directly.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE